Weekly azathioprine pulse versus betamethasone oral mini-pulse in the treatment of moderate-to-severe alopecia areata - Prashant Gupta; Kaushal K Verma; Sujay Khandpur; Neetu Bhari (Wolters Kluwer Medknow Publications, 2019)
Background: Corticosteroids are the most common agents used in the treatment of alopecia areata (AA), however, their long-term use is associated with severe side effects. Therefore, other immunosuppressive agents have been tried and azathioprine appears to be an effective and promising alternative. Objective: The main objective of this study was to compare the efficacy of 300 mg once weekly azathioprine pulse (WAP) and 5 mg betamethasone on 2 consecutive days every week in the management of AA. Materials and Methods: In this open-label, randomized comparative study, 50 patients of AA with >10% scalp area involvement were treated with either 300 mg WAP or 5 mg betamethasone on 2 consecutive days every week for 4 months or till complete scalp hair regrowth and followed up for next 5 months. Primary efficacy parameters were average percentage scalp hair regrowth and change in average Severity of Alopecia Tool (SALT) score at 4 months. Results: Twenty patients in WAP group and 21 patients in betamethasone group completed the study. The median percent scalp hair regrowth and the median change in SALT score was 44.52 and 9.5 in WAP group compared to 71.43 and 14 in betamethasone group at 4-month, respectively, which were statistically similar in two groups, however, side effects were significantly higher in betamethasone group. On further follow-up at 9 months, 10 (50%) patients in WAP group and 13 (62%) patients in betamethasone group achieved complete hair regrowth. Lack of control group was a limitation of our study. Conclusion: WAP and betamethasone therapy, both appear to be effective in the treatment of AA. However, betamethasone caused several side effects; therefore, WAP can be used as a better alternative to corticosteroids in AA.